STUDI NILAI TRANSFER PANAS KESELURUHAN PADA SELUBUNG BANGUNAN PUSAT KEGIATAN MAHASISWA - Efiariza, Restika Rahmadona; Hikmah, Nurul; Christy Damanik, Novita Hillary; Ayutia, Galuh Talitha (Jurnal Ilmiah Poli Rekayasa, 2025)
The building envelope plays a crucial role in controlling heat transfer from the outside environment to the interior of the building, which in turn affects occupant comfort and building energy consumption. This study aims to determine the existing Overall Thermal Transfer Value (OTTV) of the Student Activity Center of Universitas Indonesia (PUSGIWA UI) building, as per the applicable Indonesian National Standard (SNI). As well as providing optimization solutions to obtain OTTV values that comply with the Indonesian national standards. The OTTV calculation results of the PUSGIWA UI building show a value of 37.80 W/m², which exceeds the SNI standard limit of 35 W/m². This indicates that the building envelope at PUSGIWA UI is not yet effective in protecting and maintaining the thermal comfort conditions within the building environment. The highest OTTV value is found on the north orientation side of the building, at 42.77 W/m². As optimization, it is recommended to replace the glass section with Asahimas Sunergy Clear glass, which has a low reflection value and better solar energy shading capability compared to the existing glass. The application of this glass can reduce the OTTV value to 28.96 W/m², which already meets the thermal comfort standards of a building. This study contributes to the planning of more environmentally friendly building envelope designs and energy efficiency.